(3GdCOhjI GdeaQOI hGdeSgdIs - (3GdfLjH GdSeQbfOj , eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO,J (B619 (3g` s
(3ChdgG (B:s
(3gPG GdeNJUQ jfWhi Ydi PcQ GdCOhjI GdeaQOI GdeSJYedI hNhGUgG hCaYGdgG GdefShHI EdjgG MQha GdCda (B: (3Ecdjd (B: (3MGQ jGHS ai Gdhdi eMdd GdChQGe NGUI ai GdCYVGA GdYUHGfjI , hefVL dgG , ebhi dLejY GdCYVGA s
(3BNQgG (B:s
(3hjfHZi Cf jchf GdeYJUQ efg GdMdh hGdMGeV eYkG , dCfg CHdZ ai ESgGdg hJWaFJg GdMQGQI hGddg GdgGOi s
(3Vef eLehY s
(3GfXQgG eY OaY GdSehe Qbe (B" 467"s
(3fSNI KGfjI ef GdbSe GdKGfi ef GdfLjHjGJs
(3hJTJed Ydi GdCOhjI GdeaQOI abWs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs